High Origin of the Superficial Palmar Branch of the Radial Artery: Anatomical Variation and Clinical Implications for Thenar Flaps - Wallance Geovane Alexandre Lima; Gilvan Paixão Santos Junior; Lucas Morais Paixão; Giovanna de Oliveira Sá Costa; Adler Oliveira Silva Jacó Carvalho; Henrique Montalvão Routman da Cunha; Iapunira Catarina Sant’Anna Aragão; Felipe Matheus Sant’Anna Aragão; Francisco Prado Reis; Deise Maria Furtado de Mendonça; José Aderval Aragão (Anatomia, 2026)
Introduction: The superficial palmar branch of the radial artery (SPBRA) typically arises from the radial artery 10 to 20 mm proximal to the distal wrist crease, before the radial artery curves dorsally around the carpal bones toward the dorsum of the hand. From its origin, the SPBRA courses toward the palmar aspect of the hand, traverses the fibers of the thenar muscles, and typically anastomoses with the ulnar artery to contribute to the superficial palmar arch. Anatomical variations involving this branch have been described in the literature. Given its potential use as a vascular pedicle for thenar flaps in the reconstruction of distal finger and hand injuries, knowledge of its morphology is essential for surgical safety. Objective: To report a high origin of the SPBRA and discuss its possible clinical and surgical implications. Case Report: During routine dissection, an anatomical variation in the origin of the SPBRA was identified in an isolated right upper limb disarticulated at the elbow. The radial artery followed its usual course along the anterior aspect of the forearm and gave rise to the SPBRA in the distal third, 61.05 mm proximal to the most distal transverse wrist crease. The SPBRA coursed obliquely in a distal and medial direction, entered the fibers of the abductor pollicis brevis muscle, and, after traversing this intramuscular segment, anastomosed with the ulnar artery to form the superficial palmar arch. The straight-line distance between the origin of the SPBRA and its distal anastomosis was 92.68 mm. Conclusions: A high origin of the SPBRA is a rare anatomical variation with potential clinical relevance. Awareness of this variation may assist in planning surgical and reconstructive procedures of the hand, particularly thenar flaps. In addition to corroborating previous reports, the present study provides a quantitative morphometric description of the distance between the high origin of the SPBRA and the most distal transverse wrist crease, contributing to the anatomical characterization of this variation.